A Liquid–Solid Interface-Based Triboelectric Tactile Sensor with Ultrahigh Sensitivity of 21.48 kPa−1 - Jingya Liu; Zhen Wen; Hao Lei; Zhenqiu Gao; Xuhui Sun (Nano-Micro Letters, 2022)
Abstract Traditional triboelectric tactile sensors based on solid–solid interface have illustrated promising application prospects through optimization approach. However, the poor sensitivity and reliability caused by hard contact-electrification still poses challenges for the practical applications. In this work, a liquid–solid interface ferrofluid-based triboelectric tactile sensor (FTTS) with ultrahigh sensitivity is proposed. Relying on the fluidity and magnetism of ferrofluid, the topography of microstructure can be flexibly adjusted by directly employing ferrofluid as triboelectric material and controlling the position of outward magnet. To date, an ultrahigh sensitivity of 21.48 kPa−1 for the triboelectric sensors can be achieved due to the high spike microstructure, low Young’s modulus of ferrofluid and efficient solid–liquid interface contact-electrification. The detection limit of FTTS of 1.25 Pa with a wide detection range to 390 kPa was also obtained. In addition, the oleophobic property between ferrofluid and poly-tetra-fluoro-ethylene triboelectric layer can greatly reduce the wear and tear, resulting in the great improvement of stability. Finally, a strategy for personalized password lock with high security level has been demonstrated, illustrating a great perspective for practical application in smart home, artificial intelligence, Internet of things, etc.